Pengaruh Religiusitas Terhadap Depresi Pada Lansia Yang Tinggal di Panti Werdha - Prabasari, Ninda Ayu; Sari, Ni Putu Wulan Purnama; Freitas, Ana Aniceta Do Ceo Quadro (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2022)
One of the developmental tasks of the elderly is to increase spirituality by getting closer to God. In individuals who embrace a certain religion, spirituality is closely related to religiosity which involves religious rituals and activities. Religious appreciation has a greater influence on the physical and mental health of the elderly. This study aimed to analyze the influence of religiosity towards depression in institutionalized elderly. Methods: This cross-sectional study involved 40 Catholic elderly living in nursing home. The variables of religiosity and depression were measured by valid and reliable CRS and GDS instruments. Linear regression test was used in data analysis. Results: The majority were very religious (65%) and did not experience depression (62%). Religiosity significantly affected depression in the elderly (p=0.018). Religiosity determined 13.8% variance of depression in the elderly (R2=0.138). Discussion: The elderly have a higher desire to get closer to God than younger ages. Elderly who have religious beliefs will feel strong and experience inner peace so that there is no depressive feeling. Conclusion: Religiosity significantly influence depression in the elderly. Religiosity determines 13.8% variance of depression in institulionalized elderly.